217k views
2 votes
If k(x) = 5x – 6, which expression is equivalent to (k + k)(4)?

User Charlette
by
5.8k points

2 Answers

4 votes
(k + k)(4) =
5x - 6 + 5x - 6 = 10x - 12 =
10(4) - 12 = 40 - 12 = 28
The answer is 28
User Blacelle
by
5.9k points
2 votes

Answer:

Expression equivalent to (k + k)(4) is 28.

Explanation:

Given:

k(x) = 5x - 6

We need to find expression equivalent to (k + k)(4)

First we find,

(k + k)(x) = k(x) + k(x)

= ( 5x - 6 ) + ( 5x - 6 )

= 5x - 6 + 5x - 6

= 5x + 5x - 6 - 6

= 10x - 12

Now, (k + k)(4) = 10(4) - 12 = 40 - 12 = 28

Therefore, Expression equivalent to (k + k)(4) is 28.

User Markus Heberling
by
5.5k points